2003
DOI: 10.1177/00030651030510031501
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation and the Parent-Infant Dialogue: a Longitudinal Perspective From Attachment Research

Abstract: Two longitudinal attachment studies of families at social risk have now followed their cohorts of infants to late adolescence. Several key findings have emerged related to outcomes of interest to psychoanalysts. First, data from both studies indicate that disorganized attachment behaviors in infancy are important precursors of later dissociative symptomatology. Second, this early vulnerability is related to patterns of parent-infant affective communication, particularly quieter behaviors like emotional unavail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
127
0
10

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(140 citation statements)
references
References 27 publications
3
127
0
10
Order By: Relevance
“…Attachment system is among the fundamental action systems regulating responses to threats and preventing their interference to the daily action systems. When the attachment system is disrupted, individuals tend to focus more on issues like security and safety and ignore their development in other areas such as exploring, learning and establishing interpersonal relationships (daily action systems) [51]. Due to the aforementioned disruption, adults who were exposed to childhood trauma are likely to develop impaired attachment types with their partners.…”
Section: Discussionmentioning
confidence: 99%
“…Attachment system is among the fundamental action systems regulating responses to threats and preventing their interference to the daily action systems. When the attachment system is disrupted, individuals tend to focus more on issues like security and safety and ignore their development in other areas such as exploring, learning and establishing interpersonal relationships (daily action systems) [51]. Due to the aforementioned disruption, adults who were exposed to childhood trauma are likely to develop impaired attachment types with their partners.…”
Section: Discussionmentioning
confidence: 99%
“…The action associated with this kind of normal projective process is likely to be sexual exploration (Fonagy & Target, in This process relates directly to the falling back on a focus on the physical self when there is a loss of social contingency, which we have discussed before. We saw that infants with disorganised attachment, exposed in the first year of life to unpredictable loss of contingent reactions (Goldberg et al, 2003;Lyons-Ruth, 2003), react by creating a highly predictable experience, looking at themselves. We anticipate that these individuals will have grave difficulty in engaging in the kind of normal projective identificatory process described above.…”
Section: Linking To the Private World Of Othersmentioning
confidence: 99%
“…Under these conditions, neural networks related to daily life action systems become increasingly more complex and interactive through constant and consistent use, leading to a more cohesive personality and an individual who is well adapted to life with others (Lyons-Ruth, 2003).…”
Section: Developmental Pathways To Structural Dissociationmentioning
confidence: 99%
“…Research and clinical observations have shown a strong link between disordered parental attachment, disorganized/disoriented attachment in the child, and chronic dissociation (Barach, 1991;Carlson, 1998;Liotti, 1992Liotti, , 1999Lyons-Ruth, 2003;Ogawa et al, 1997). Young children's innate attachment system evokes mental and behavioral approach when they are separated from their caregiver.…”
Section: Developmental Pathways To Structural Dissociationmentioning
confidence: 99%
See 1 more Smart Citation